KETIKA HAKIM BERBEDA PENDAPAT - Andreas Eno Tirtakusuma (Program Magister Ilmu Hukum Universitas Pancasila, 2019)
in deciding a case by a panel of judges with composition of at least three judges, it will make any possibility for any judge make different opinion between one judge and another, even though the decision should be based on unanimous deliberation. If they cannot reach the unanimous deliberation, then the decision shall be taken with voting. The different opinion, that is “dissenting opinions,” must still be included in the decision. There are two types of dissenting opinions, they are the